Dengue viremia kinetics and effects on platelet count and clinical outcomes: an analysis of 2340 patients from Vietnam - Vuong, Nguyen Lam; Quyen, Nguyen Than Ha; Tien, Nguyen Thi Hanh; Duong Thi Hue, Kien; Duyen, Huynh Thi Le; Lam, Phung Khanh; Tam, Dong Thi Hoai; Van Ngoc, Tran; Jänisch, Thomas; Simmons, Cameron P.; Yacoub, Sophie; Wills, Bridget A.; et al. (eLife, 2024)
BACKGROUND: Viremia is a critical factor in understanding the pathogenesis of dengue infection, but limited data exist on viremia kinetics. This study aimed to investigate the kinetics of viremia and its effects on subsequent platelet count, severe dengue, and plasma leakage. - METHODS: We pooled data from three studies conducted in Vietnam between 2000 and 2016, involving 2340 dengue patients with daily viremia measurements and platelet counts after symptom onset. Viremia kinetics were assessed using a random effects model that accounted for left-censored data. The effects of viremia on subsequent platelet count and clinical outcomes were examined using a landmark approach with a random effects model and logistic regression model with generalized estimating equations, respectively. The rate of viremia decline was derived from the model of viremia kinetics. Its effect on the clinical outcomes was assessed by logistic regression models. - RESULTS: Viremia levels rapidly decreased following symptom onset, with variations observed depending on the infecting serotype. DENV-1 exhibited the highest mean viremia levels during the first 5-6 days, while DENV-4 demonstrated the shortest clearance time. Higher viremia levels were associated with decreased subsequent platelet counts from day 6 onwards. Elevated viremia levels on each illness day increased the risk of developing severe dengue and plasma leakage. However, the effect size decreased with later illness days. A more rapid decline in viremia is associated with a reduced risk of the clinical outcomes. - CONCLUSIONS: This study provides comprehensive insights into viremia kinetics and its effect on subsequent platelet count and clinical outcomes in dengue patients. Our findings underscore the importance of measuring viremia levels during the early febrile phase for dengue studies and support the use of viremia kinetics as outcome for phase-2 dengue therapeutic trials. - FUNDING: Wellcome Trust and European Union Seventh Framework Programme.